Molecular characterization of bacterial populations of different soils - Pereira, Rodrigo Matheus [UNESP]; Silveira, Érico Leandro da [UNESP]; Scaquitto, Denilson César [UNESP]; Pedrinho, Eliamar Aparecida Nascimbém [UNESP]; Val-Moraes, Silvana Pompéia [UNESP]; Wickert, Ester [UNESP]; Carareto-Alves, Lúcia Maria [UNESP]; Lemos, Eliana Gertrudes de Macedo [UNESP] (Sociedade Brasileira de Microbiologia, 2006)
Até o momento poucos estudos foram realizados no Brasil a respeito da diversidade de comunidades bacterianas no solo. Com o objetivo de caracterizar as populações bacterianas presentes no solo através da análise do gene 16S rRNA, foram analisados dois solos: um caracterizado pelo uso intensivo, principalmente para a produção de tomate, feijão e milho (CS); e outro sob floresta (FS), não modificado pelo homem, ambos do município de Guaíra, no estado de São Paulo, Brasil. Usando oligonucleotídeos específicos, de genes 16S rRNA do DNA metagenomico de ambos os solos foram amplificados por PCR, amplicons foram clonados e 139 clones de duas bibliotecas foram seqüenciados. O uso da técnica de 16S rRNA, gerou a identificação de diferentes populações de bactérias de solo pertencentes aos filos Acidobacteria Actinobacteria Bacteroidetes Firmicutes Proteobacteria Verrucomicrobia, Archaea, além das não classificadas. Diferenças entre as bibliotecas FS e CS foram observadas no tamanho dos filos. Um grande número de filos e, consequentemente, uma grande diversidade bacteriana foi observada no solo sob floresta. Estes dados foram confirmados pela análise de diversidade genética realizada. A caracterização de comunidades do solo apresentada neste trabalho contribuiu fornecendo dados para estudos posteriores sobre a dinâmica das populações bacterianas em solos de diferentes condições no Brasil.

Until recently, few studies were carried out in Brazil about diversity of bacterial soil communities. Aiming to characterize the bacterial population in the soil through 16S rRNA analysis, two types of soil have been analyzed: one of them characterized by intensive use where tomato, beans and corn were cultivated (CS); the other analyzed soil was under forest (FS), unchanged by man; both located in Guaíra, São Paulo State, Brazil. Using specific primers, 16S rRNA genes from metagenomic DNA in both soils were amplified by PCR, amplicons were cloned and 139 clones from two libraries were partially sequenced. The use of 16S rRNA analysis allowed identification of several bacterial populations in the soil belonging to the following phyla: Acidobacteria, Actinobacteria, Bacteroidetes, Firmicutes, Proteobacteria Verrucomicrobia in addition to the others that were not classified, beyond Archaea domain. Differences between FS and CS libraries were observed in size phyla. A larger number of phyla and, consequently, a greater bacterial diversity were found in the under-forest soil. These data were confirmed by the analyses of genetic diversity that have been carried out. The characterization of bacterial communities of soil has made its contribution by providing facts for further studies on the dynamics of bacterial populations in different soil conditions in Brazil.
Caracterização molecular de populações bacterianas de diferentes solos
Keywords: Metagenome; microbial diversity; 16S rRNA; Metagenôma; diversidade microbiana; rRNA 16S